Impelementasi Kebijakan Pelayanan Perijinan Usaha Pasar Modern di Kota Cirebon (Studi Kasus di Kecamatan Kesambi) - Mely Marlya; Nurudin Siraj; Rifai Yusuf (Universitas Swadaya Gunung Jati, 2014)
ABSTRACT The modern market is not much different from the traditional market, but the market of this type of seller and buyer does not transact directly but the buyer sees the price tag listed in the barcode, is in the building and the service is self-service or serviced by the sales clerk. Items sold, other than foodstuffs such as food; fruit, vegetables, meat; most of the other items sold are goods that can last a long time. Examples of modern markets are hypermarts, supermarkets (supermarkets), and minimarkets. Modern markets in this sense, including minimarkets, supermarkets, hypermarkets. Most of the owners of this modern market are big businessmen. It is undeniable that the existence of modern markets has now become the demands of the consequences of a thriving lifestyle in our society. Modern market is not only a place to shop but also other activities, such as just a walk, hang out with friends and family.This writing aims to describe Implementation Policy Service License Market Modern Business in Cirebon City, Case Study in Kecamatan Kesambi. The background does this writing because in this case it is the other side that the implemented policy implementation has not run optimally.This writing is directed to know the extent to which the implementation of policies on the development and licensing of modern markets by the Department of Industry, Trade and Cooperative Micro Small Medium Enterprises Cirebon City, and the Investment Board and Licensing Services Cirebon City in a case study in Kecamatan Kesambi, and factors anything that affects the implementation.The writing method used is using qualitative method through descriptive approach, by taking the location of writing at Department of Industry, Trade, and Cooperative Micro Small Medium Enterprises of Cirebon City, and Capital Investment and Licensing Service of Cirebon City in case study in Kecamatan Kesambi, Key informants in this paper are the Head of Industry, Domestic Trade and Economic Section, Kecamatan Development of Kesambi and then informants supporting the Staff of Industry Sector, Domestic Trade of Cirebon City, Head of the Cirebon City Licensing Service, Head of Kesambi sub-district, Kesambi Community.